Evidence for an ancient association between leaf mining flies and herbaceous eudicot angiosperms. (August 2016) - Jud, Nathan A.; Sohn, Jae-Cheon
Abstract: We describe an early angiosperm and a leaf mine ichnofossil from the Lower Cretaceous Potomac Group of Virginia, USA. The descriptions are based on a fossil leaf that was first reported in 1895 but identified as a fragment of a fossil fern. The new genus and species of angiosperm, Vernifolium tenuiloba Jud and Sohn, gen. et sp. nov., was likely herbaceous and is based on a twice odd-pinnatifid leaf with glandular teeth at the tips of the lobes, and minute resin bodies covering the lamina. Leaf architectural features and sedimentological context indicate that this leaf was produced by an herbaceous eudicot angiosperm, possibly associated with Ranunculales. The leaf mine Phytomyzites wardi Sohn and Jud, ichnosp. n. is a full depth linear-blotch mine with frass, a trace of puparium inside the blotch mine section, and feeding/oviposition-related puncture marks. The features of the mine are most consistent with those produced by agromyzid flies. This fossil extends the record of agromyzid flies by about 40 myr. Furthermore, data from molecular studies suggests that the ancestral hosts for agromyzid flies are asterids, with several later host-shifts to feeding on Ranunculaceae, but this fossil provides evidence that agromyzid flies or their ancestors were feeding on herbaceous basal eudicots similar to modern herbaceous ranunculids during the Early Cretaceous, prior to the appearance and diversification of asterids. Highlights: We describe a fossil leaf mine on an early angiosperm from the Lower Cretaceous of Eastern North America. This study represents the oldest evidence of agromyzid flies, suggesting their Cretaceous diversification. This study supports an ancient association with herbaceous angiosperms and more recent shifts to woody lineages. The modern diversity of Agromyzidae was shaped by extinction plus evolutionary radiations following host-shifts.